The student response on the use of renewable energy graphical interface simulator in learning environment - Lavaniya Gopabala Krishnan, Lavaniya Gopabala Krishnan; Aliashim Albani, Aliashim Albani; Yogesswary Segar, Yogesswary Segar; Ridzuan, Abdul Rahim; Ismail, Mohd Khairi; Musa, Mohd Azlan; Khemaalatha Gunaseelan, Khemaalatha Gunaseelan; Tamil Selvan Subramaniam, Tamil Selvan Subramaniam; Ibrahim, Mohd Zamri (Frontier, 2023)
The purpose of this study is to evaluate students’ responses regarding the usefulness of a graphical user interface (GUI) tool in the context of their respective learning environments. The Energy Computator GUI (EC-GUI) helps to simplify the STEM student’s learning processes. The EC-GUI serves as a simulator that can assist in computing formulas, designing graphs, acting as a unit converter, and automatically deriving parameters.